Investigating The Vocabulary Level In Foreign Language Learners: An Explanatory Study In High Education - Faiz Nadir Roidatul Jannah; Ghozali, Imam (Linguapedia, 2024)
This study, will investigate the vocabulary level of foreign language learners in 4th semester at Islamic University of Jember. This study was adopted mixed methods research, combines both qualitative and quantitative methods to collecting and analysing the data that help the research objectives. The explanatory sequential in which qualitative and quantitative data were collected sequentially in two ways was used. The researcher conducted 2 tests, the first is Vocabulary Level Test (VLT) and second is interview. Vocabulary Level Test to find out the average of students' vocabulary level at English Department. And the interview test to investigate how does the students vocabulary development exists in English Department, Faculty of Teacher Training and Education Islamic University of Jember.